Analisa Performansi Tanggapan Tegangan Sistem Eksitasi Generator Terhadap Perubahan Parameter - Heru Dibyo Laksono; Adry Febrianda (JURNAL NASIONAL TEKNIK ELEKTRO, 2015)
This journal discusses about performance analysis of generator excitation system voltage response towards parameters changes. Changes in the parameters of the generator excitation system will affect the response voltage generator excitation system performance, in both time domain and frequency domain performances. The performance analysis of the generator excitation system voltage response in both time domain and frequency domain, conduct with the help of Matlab software. For performance in the time domain is consists of error analysis and transient analysis, while for performance in the frequency domain is consists of the open-loop performance and closed-loop performance. The parameters that to be changed are the amplifier gain constant, amplifier time constant, generator gain constant, and generator time constant. The analysis result shows that the performance of the generator excitation system voltage response in both time domain and frequency domain performances is very sensitive towards the changes in the parameters, especially for the changes of amplifier gain constant, the changes of amplifier time constant, the changes of generator gain constant, and the changes of generator time constant.